Pd-Rh-Ni three-dimensional network-shaped metal material as well as preparation method and application thereof

By using Pd-Rh-Ni three-dimensional network metal material as oxygen reduction electrocatalyst, using cyano gel template and room temperature reduction technology, the problems of slow kinetics of cathodic oxygen reduction reaction and limited palladium reserves in the existing technology are solved, and the problem of slow cathodic oxygen reduction reaction in the existing technology is achieved. High activity and stability of oxygen reduction performance under alkaline conditions and significantly improves the power density of fuel cells.

CN119481108AActive Publication Date: 2025-02-18NANTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411591714.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The prior art has slow kinetics in cathode oxygen reduction reaction under alkaline conditions and limited reserves of palladium, making it difficult to achieve effective application of high reactive oxygen reduction electrocatalysts.

Method used

The Pd-Rh-Ni three-dimensional network metal material was used as the oxygen reduction electrocatalyst, and the cyano gel was used as the template, and the simple and efficient room temperature reduction technology was used to prepare metal alloy nanoparticles with excellent activity and stability.

Benefits of technology

High oxygen reduction activity and excellent stability under alkaline conditions are achieved, and the power density of the anion exchange membrane fuel cell is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481108A_ABST
    Figure CN119481108A_ABST
Patent Text Reader

Abstract

The invention discloses a Pd-Rh-Ni three-dimensional network-shaped metal material as well as a preparation method and application thereof. The preparation method mainly comprises the following steps: S1, preparing a Pd-Rh-CN-Ni cyanogen glue precursor material; and S2, reducing the Pd-Rh-CN-Ni cyanogen glue by using NaBH4 at normal temperature, stirring, standing, freeze-drying, centrifuging and washing to obtain the Pd-Rh-Ni three-dimensional network alloy. According to the method, the selected raw materials are cheap and easy to obtain, the process is simple and easy to implement, the prepared material shows excellent activity and stability when being used as the positive electrode of the anion exchange membrane fuel cell and shows good power density when being used as the positive electrode of the anion exchange membrane fuel cell, and a new application material is provided for the energy industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of anion exchange membrane fuel cells, and specifically relates to a Pd-Rh-Ni three-dimensional network metal material and a preparation method and application thereof. Background Art

[0002] Hydrogen-oxygen fuel cells convert the chemical energy in hydrogen and oxygen directly into electrical energy. It is an electrochemical reaction, and its essence is the change from internal energy to electrical energy, and the type of energy has changed. As long as the reaction can occur, the energy can be smoothly converted without considering the temperature difference and the influence of temperature, so it will not be affected by the efficiency of the Carnot cycle heat engine. This not only improves the efficiency of energy utilization, but also the clean and pollution-free reaction products of fuel cells can also play a role in protecting the environment. At the same time, it can be distributed for power generation, has a relatively small size and low noise. Increasing its fuel can increase its power generation capacity, so fuel cells can be considered the most suitable hydrogen energy utilization device.

[0003] The kinetics of the cathode oxygen reduction reaction is slow under alkaline conditions. To improve its reaction activity, a highly active precious metal palladium-based catalyst is required. However, the reserves of palladium in nature are very limited. Anion exchange membrane fuel cells have attracted much scientific research attention due to their low cell noise, low operating temperature, high energy conversion efficiency, fast startup speed, and especially the fast kinetics of oxygen reduction reaction in alkaline environments. Therefore, the search for highly active oxygen reduction electrocatalysts for application in the field of anion exchange membrane fuel cells has great theoretical and practical significance.

[0004] In recent years, three-dimensional (3D) nanomaterials have attracted much attention for their high porosity, large specific surface area and unique three-dimensional interconnected structure. Cyanide gel is a highly hydrophilic insoluble cyanide-bridged bimetallic coordination polymer. When cyanide metallate meets chlorometallate, a chain configuration is generated by replacing the chlorine ligand with the middle end of the cyanide ligand, thereby showing typical polymer characteristics and improving chemical stability. Although pure palladium has excellent oxygen reduction performance, its cost is very expensive. The use of medium-entropy alloy catalysts can not only reduce the amount of pure palladium used, but also greatly improve the performance of the catalyst. Therefore, the preparation of multi-element nanocatalysts is a feasible strategy. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a Pd-Rh-Ni three-dimensional network metal material and a preparation method and application thereof. The preparation method of the present invention is simple, universal and low-cost. The obtained Pd-Rh-Ni three-dimensional network metal material exhibits excellent activity and stability as an oxygen reduction electrocatalyst material, and exhibits good power density as the positive electrode of anion exchange membrane fuel cell, providing a new application material for the energy industry.

[0006] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:

[0007] A method for preparing a Pd-Rh-Ni three-dimensional network metal material comprises the following steps:

[0008] S1. preparing Pd-Rh-CN-Ni precursor cyanoacrylate material;

[0009] S2. The Pd-Rh-CN-Ni precursor cyanoacrylate material is reduced by using NaBH4 solution, stirred at 300-500 r / min for 12-24 h at 0-10° C., then freeze-dried, centrifugally washed, and dried to obtain a Pd-Rh-Ni three-dimensional network metal material.

[0010] Preferably, the Pd-Rh-CN-Ni precursor cyanide gel material described in step S1 is prepared by mixing K2PdCl4 solution and RhCl3 solution by ultrasonication, adding K2Ni(CN)4 solution, continuing ultrasonication in an ice water bath, and standing to obtain the Pd-Rh-CN-Ni precursor cyanide gel material.

[0011] It is further preferred that the mass of K2PdCl4 solid in the K2PdCl4 solution is 30-40 mg.

[0012] It is further preferred that in the RhCl3 solution, the mass of RhCl3 solid is 15-20 mg;

[0013] It is further preferred that in the K2Ni(CN)4 solution, the mass of K2Ni(CN)4 is 30-40 mg.

[0014] Preferably, the concentration of NaBH4 in step S2 is 15-40 mg / mL.

[0015] As an improvement, the freeze-drying temperature in step S2 is between -40°C and -50°C, and the drying temperature is not higher than 60°C.

[0016] The Pd-Rh-Ni three-dimensional network metal material prepared by the above preparation method.

[0017] The above-mentioned Pd-Rh-Ni three-dimensional network metal material is used as a catalyst in alkaline oxygen reduction reaction.

[0018] As an improvement, the application is as a positive electrode material in an anion exchange membrane fuel cell.

[0019] Beneficial effects:

[0020] Compared with the prior art, the present invention provides a Pd-Rh-Ni three-dimensional network metal material and its preparation method and application, with potassium chloropalladate, rhodium chloride and nickel potassium cyanide as metal sources, and using the unique three-dimensional structure of cyanogel as a template, so that the metal grows along the three-dimensional skeleton of cyanogel, greatly promoting the transfer of mass / charge, generating more active sites, and preventing the dissolution, migration and even aggregation of metal nanoparticles during the reaction. In addition, since multiple metals are uniformly mixed at the atomic level, the solid properties of the obtained cyanogel will inhibit the migration of metal atoms during the reduction process, thereby forming metal alloy nanoparticles with a highly uniform structure, and the obtained material has high oxygen reduction activity and excellent stability under alkaline conditions. Specifically, the present invention can obtain a Pd-Rh-Ni three-dimensional network metal material through a simple, efficient and rapid room temperature reduction technology, and the obtained metal alloy nanoparticles have a regular morphology, high uniformity, and a unique three-dimensional structure, which greatly promotes the transfer of mass / charge. Thus, the obtained material has many active sites, high half-wave potential and good stability. Compared with conventional Pd-based precious metal materials, the Pd-Rh-Ni three-dimensional network metal material of the present invention has more excellent structural characteristics and component advantages. It is a very potential oxygen reduction electrocatalyst material, exhibits good power density in anion exchange membrane fuel cells, and is expected to have broad application prospects in the future energy industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the SEM spectrum of the Pd-Rh-Ni three-dimensional network metal material prepared in Example 1;

[0022] Figure 2 TEM spectrum of the Pd-Rh-Ni three-dimensional network metal material prepared in Example 1;

[0023] Figure 3 The XRD pattern of the Pd-Rh-Ni three-dimensional network metal material prepared in Example 1;

[0024] Figure 4 The LSV curve of the Pd-Rh-Ni three-dimensional network metal material prepared in Example 1;

[0025] Figure 5 The Tafel curve of the Pd-Rh-Ni three-dimensional network metal material prepared in Example 1;

[0026] Figure 6 Polarization (black) and corresponding power density curve (gray) of the Pd-Rh-Ni three-dimensional network metal material prepared in Example 1;

[0027] Figure 7The LSV curves of the materials obtained in Example 1 and Comparative Examples 1 to 3 of the present invention are compared. DETAILED DESCRIPTION

[0028] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0029] Example 1

[0030] A method for preparing a Pd-Rh-Ni three-dimensional network metal material comprises the following steps:

[0031] 1) Preparation of Pd-Rh-CN-Ni precursor cyanoacrylate material:

[0032] Weigh 36 mg K2PdCl4, 16 mg RhCl3, and 36 mg K2Ni(CN)4 and disperse them in 2 ml deionized water respectively. Then, ultrasonically mix the dispersed K2PdCl4 solution and RhCl3 solution in a room temperature water bath for 5 minutes. Then, add the dispersed K2Ni(CN)4 solution and ultrasonically mix them in an ice water bath for 5 minutes to obtain the Pd-Rh-CN-Ni precursor cyanide gel material.

[0033] 2) Preparation of Pd-Rh-Ni three-dimensional network metal material:

[0034] The Pd-Rh-CN-Ni precursor cyanoacrylate material prepared in step 1) was reduced by adding 10 ml of 18.9 mg / ml NaBH4 at 25°C. The reduction reaction was carried out under sealed stirring for 12 hours, and then placed in a refrigerator for freezing after standing for 2 hours. The frozen solid was then transferred to a freeze dryer for freeze drying, and the freeze drying temperature was maintained at -45°C. Finally, the freeze-dried material was washed twice with water and ethanol, and finally dried at room temperature to obtain a Pd-Rh-Ni three-dimensional network metal material.

[0035] The Pd-Rh-Ni three-dimensional network metal material prepared in the above example was physically characterized by SEM, HR-TEM, XRD and the like.

[0036] Figure 1 This is the SEM of the Pd-Rh-Ni three-dimensional network metal material. From the figure, it can be seen that the material has a three-dimensional network morphology, indicating that the material successfully constructs a three-dimensional network structure through cyanamide glue.

[0037] Figure 2This is the HR-TEM spectrum of the Pd-Rh-Ni three-dimensional network metal material. From the figure, it can be seen that the Pd-Rh-Ni three-dimensional network metal material has different lattice spacings and clear lattice fringes, which further illustrates the formation of the ternary alloy.

[0038] Figure 3 This is the XRD spectrum of the Pd-Rh-Ni three-dimensional network metal material. It can be seen from the figure that the diffraction peak of the material is between the standard cards of Pd, Rh, and Ni (JCPDS cards, 04-0850; 05-0685; 46-1043), further proving the formation of the ternary alloy.

[0039] Figure 4 This is the LSV graph obtained by testing the oxygen reduction performance of the Pd-Rh-Ni three-dimensional network metal material. It can be seen from the figure that the initial reduction potential and half-wave potential are 0.993V and 0.85V respectively.

[0040] Tafel curve Figure 5 ) shows that the value of the Tafel slope of this material is better than that of most alkaline oxygen reduction electrocatalyst materials.

[0041] Figure 6 It is the polarization and corresponding power density curve of Pd-Rh-Ni three-dimensional network metal material as the positive electrode material of anion exchange membrane fuel cell.

[0042] Combination Figure 1-5 as well as Figure 6 It can be seen from the analysis that the Pd-Rh-Ni three-dimensional network metal material of the present invention has the following advantages:

[0043] 1) The particle size of the Pd-Rh-Ni three-dimensional network metal material is small, between 2-10nm, and has excellent electrochemical activity and more catalytic active sites;

[0044] 2) The addition of transition metals regulates the Pd-Pd electronic structure and bond length, and reasonably reduces the Pd loading;

[0045] 3) Using cyanogel as a template, its unique three-dimensional network structure can greatly promote the transfer of mass / charge and produce more active sites. Its alloyed surface contains rich atomic defects that change the structure of pure metal atoms. At the same time, cyanogel also has the ability of surface self-cleaning, and can remove pollution on the surface of the material under simple external force conditions. Cyanogel and its derivative materials also have broad application prospects in fuel cells and multiphase catalysis.

[0046] Example 2

[0047] Except that the amount of K2Ni(CN)4 in step 1) is changed to 40 mg, the rest is the same as Example 1.

[0048] Example 3

[0049] Except that the amount of RhCl3 in step 1) is changed to 20 mg, the rest is the same as Example 1.

[0050] Example 4

[0051] Except that the amount of K2PdCl4 used in step 1) is changed to 15 mg, the rest is the same as Example 1.

[0052] Example 5

[0053] Except for 30 mg K2PdCl4, 20 mg RhCl3, and 40 mg K2Ni(CN)4 in step 1), the rest is the same as in Example 1.

[0054] Example 6

[0055] Except for 36 mg K2PdCl4, 20 mg RhCl3, and 40 mg K2Ni(CN)4 in step 1), the rest is the same as in Example 1.

[0056] Example 7

[0057] Except that the volume of NaBH4 in step 2) is changed to 5 ml, the rest is the same as Example 1.

[0058] Example 8

[0059] Except that the stirring time in step 2) is 20 h, the rest is the same as in Example 1.

[0060] Example 9

[0061] Except that the concentration of NaBH4 in step 2) is changed to 25 mg / ml, the rest is the same as Example 1.

[0062] Example 10

[0063] Except that the concentration of NaBH4 in step 2) is changed to 16 mg / ml, the rest is the same as Example 1.

[0064] Comparative Example 1

[0065] The difference from Example 1 is that only metal salts K2PdCl4 and K2Ni(CN)4 are used, and the other conditions remain unchanged.

[0066] Comparative Example 2

[0067] The difference from Example 1 is that only metal salts K2PdCl4 and RhCl3 are used, and the other conditions remain unchanged.

[0068] The LSV test of oxygen reduction reaction was carried out on Example 1, Comparative Examples 1-2, and commercial Pt-C. The test results are as follows: Figure 7 As shown, the bimetallic Pd-Rh electrocatalytic material exhibits the smallest initial reduction potential and the smallest half-wave potential, and exhibits the worst oxygen reduction performance; the electrocatalytic materials prepared by the bimetallic metal Pd-Ni all show poorer oxygen reduction performance than the Pd-Rh-Ni three-dimensional network metal material. The overall performance comparison shows the order of Pd-Rh-Ni (Example 1)> Commercial Pt-C>Pd-Ni (Comparative Example 1)>Pd-Rh (Comparative Example 2).

[0069] In summary, the present invention can obtain Pd-Rh-Ni three-dimensional network metal materials through a simple, efficient and rapid room temperature reduction technology. The obtained metal alloy nanoparticles have regular morphology, high uniformity, and unique three-dimensional structure, which greatly promotes the transfer of mass / charge. Therefore, the obtained material has many active sites, high half-wave potential and good stability. Compared with conventional Pd-based precious metal materials, the Pd-Rh-Ni three-dimensional network metal material of the present invention has more excellent structural characteristics and component advantages, and is a very potential oxygen reduction electrocatalyst material. It shows good power density in anion exchange membrane fuel cells and is expected to have broad application prospects in the future energy industry.

Claims

1. A method for preparing a Pd-Rh-Ni three-dimensional network metal material, characterized in that: The following steps are involved: S1. preparing Pd-Rh-CN-Ni precursor cyanoacrylate material; S2. The Pd-Rh-CN-Ni precursor cyanoacrylate material is reduced by using NaBH4 solution, stirred at 300-500 r / min for 12-24 h at 0-10° C., then freeze-dried, centrifugally washed, and dried to obtain a Pd-Rh-Ni three-dimensional network metal material.

2. The method for preparing the Pd-Rh-Ni three-dimensional network metal material according to claim 1, characterized in that: The Pd-Rh-CN-Ni precursor cyanoacrylate material described in step S1 is prepared by mixing K2PdCl4 solution and RhCl3 solution with ultrasound, then adding K2Ni(CN)4 solution, continuing ultrasound in an ice water bath, and standing to obtain the Pd-Rh-CN-Ni precursor cyanoacrylate material.

3. The method for preparing the Pd-Rh-CN-Ni precursor cyanoacrylate material according to claim 2, characterized in that: The mass of the K2PdCl4 is 15-40 mg.

4. The method for preparing the Pd-Rh-CN-Ni precursor cyanoacrylate material according to claim 2, characterized in that: The mass of RhCl3 solid is 15-20 mg.

5. The method for preparing the Pd-Rh-CN-Ni precursor cyanoacrylate material according to claim 2, characterized in that: The mass of K2Ni(CN)4 is 30-40 mg.

6. The method for preparing the Pd-Rh-CN-Ni precursor cyanoacrylate material according to claim 1, characterized in that: The concentration of NaBH4 in step S2 is 15-40 mg / mL.

7. The method for preparing the Pd-Rh-CN-Ni precursor cyanoacrylate material according to claim 1, characterized in that: The freeze-drying temperature in step S2 is between -40°C and -50°C, and the drying temperature is not higher than 60°C.

8. A Pd-Rh-Ni three-dimensional network metal material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the Pd-Rh-Ni three-dimensional network metal material according to claim 8 as a catalyst in an alkaline oxygen reduction reaction.

10. The use according to claim 9, characterized in that: The application described is the application as a positive electrode in an anion exchange membrane fuel cell.

Citation Information

Patent Citations

  • Method for preparing Pd catalyst with three-dimensional nano meshy structure by reduction of nitrile rubber precursor

    CN102389794A

  • Cyano-modified three-dimensional palladium-copper nano coral as well as preparation method and application thereof

    CN113714507A

  • Porous PdIrH alloy nano-network catalyst with three-dimensional frame structure as well as high-throughput preparation method and application of porous PdIrH alloy nano-network catalyst

    CN117894999A